EngMeta: metadata for computational engineering. (16th June 2020) - Schembera, Björn; Iglezakis, Dorothea
The huge amounts of data produced in computational engineering make the handling and documentation of the resulting data a challenge. EngMeta is a metadata model based on existing standards and developed to enable a structured documentation of the research process and the simulation environment all together with discipline specific information about the simulated system. A qualitative analysis shows that EngMeta fulfils the criteria of a good metadata model. According to a quantitative survey, EngMeta meets the needs of engineering scientists. The metadata model is defined as an XSD scheme and in practical use in an institutional data repository. Supported by automated metadata extraction and a repository, EngMeta enables specific research data management in computational engineering.